Analysis of numerical and experimental results of a solar glazed air collector configuration in Romania climate. Issue 1 (May 2021) - Sima, C; Teodosiu, C; Croitoru, C; Bode, F
Abstract: This paper proposes an experimental and numerical study (based on CFD – Computational Fluid Dynamics technique) dealing with a glazed transpired solar collector (GTC), having the distance between the glass and absorber plate of 50 mm. The behaviour of the GTC has been studied for different air flow rates. Based on the results obtained, it can be concluded that this GTC configuration behaves best for air flow rates of about 300 m 3 /h. On the other hand, further studies are needed to improve the numerical model (especially regarding the introduction of boundary conditions based on measured data).